Towards personalized cognitive-social affective engagement among active seniors: A case study on UX and inclusive design - Lee, Chien Sing *; Guy, Sheng Yee *; Chan, Wei Ling * (Asia-Pacific Society for Computers in Education, 2018)
Cognitive-socio-affective engagement is crucial to maintaining quality of life in all ages. However, as age increases and technology becomes more permissive and seamless, the question is how to design technology and content for positive user experience as well as for inclusive design. Furthermore, in contrast to the common belief that aging leads to reduced brain plasticity, some researches have indicated that the actual problem may be that seniors learn too much and the actual problem is the ability to filter out. In this paper, we investigate: a) How can we design for cognitive-socio affectivephysical engagement taking into account cognitive load, motivation theory and inclusive design? b) i) Which among the design principles are more important for a sample of Malaysian seniors? ii) What are users’ perceptions towards Augmented Reality in inclusive design? c) What are implications to inclusive design? User testing based on user experience (UX) are carried out. Based on Cognitive Load theory, Keller’s Motivation theory, Koster’s theory of fun and inclusive design, we designed for cognitive-socio-affective-physical engagement. Findings in user interface and interaction design highlight the importance of a Systems Theory approach with regards to diverse stakeholders, cognitive-socio-affective factors, UX and game mechanics prior to the development of personalised services, towards further open interoperability, richer learning analytics and better context-awareness.